Comparison of two coprological methods for the diagnosis of Eurytrema ssp. in cattle and sheep - Olmos, Leandro Hipolito; Pantiu, Andrea Julia; Avellaneda Cáceres, Agustín; Valencia, P.N.; Cayo, P.N.; Signorini Porchiett, Marcelo Lisandro; Micheloud, Juan Francisco (Cambridge University Press, 2022)
Eurytrematosis is a disease caused by flukes of the genus Eurytrema. These parasites infect the pancreatic ducts of a wide variety of species, including cattle, sheep and humans. Diagnosing eurytrematosis through the analysis of faecal samples can be difficult because most of the available techniques are considered of low sensitivity. In this context, a modification of the Dennis, Stone and Swanson technique (Belem Sedimentation Technique, BST) was previously developed to increase the probability of detecting infected animals; nevertheless, the values of eggs per gram obtained using the modified technique are generally low. We proposed a modification of the this technique (MBST), to increase the sensitivity and detection rate of infected animals. The objective of this work was to describe MBST and compare it with BST. Faecal samples of 212 clinically healthy animals (174 from cattle and 38 from sheep) from 20 farms were taken by the intra-rectal route and stored at 4°C. The samples were processed using BST and MBST. Positive samples amounted to 55 (25.9%) using BST and 121 (57.1%) using MBST. In the simples from cattle, 52 (29.8%) and 107 (61.4%) were positive in BST and MBST, respectively. In sheep, three (7.8%) and 14 (36.8%) positive samples were obtained in BST and MBST, respectively.The results obtained using the two methods were significantly different, indicating a lack of agreement between their findings. The results suggest that MBST is a more sensitive method to detect Eurytrema spp. eggs in faeces than BST.